FACTORS HINDERING STRATEGIC MANAGEMENT IN EAST JAKARTA COMPANIES - Fadhilah Yuniarti; Yulianah, Yulianah (Jurnal Ekonomi, 2022)
Strategic management is a set of decisions to achieve the superior goals of an enterprise through planning and other management tasks. There is a lot of research that discusses strategic management. However, from the large number of studies, there are not many studies that develop factors that hinder strategic management in a company. This study aims to find out how many factors hinder strategic management in a company in East Jakarta. The study used factor analysis with a quantitative type of approach. The research was conducted at a company in East Jakarta in May–June 2022. The population and samples in this study were employees who worked in companies located in East Jakarta. The sampling technique used, namely cluster random sampling, obtained a sample of 228 employees. Data collection techniques use questionnaires that are shared directly and indirectly (via google form). Data analysis techniques use factor analysis. The results showed 4 inhibiting factors formed. Factor 1 is named Complaint Management, factor 2 is named Human Resource Management, factor 3 is named Information Management System, factor 4 is named Financial Management System..